FUNERAL SONGS - Éva PÉTER (Studia Universitatis Babeş-Bolyai. Musica)
The traditional reformed community has many customs related to the three-day mourning of the dead, the period between the time of death and the time of burial. Musical performances are a crucial part of this mourning period.